Surgical tactis in gastric polyps - Barg, Salomón; Caniparoli, Alberto; Rezzonico, Ricardo; Sánchez Briones, Pablo; Díaz, Omar; Guillermo Frank, Luis (Cirugía del Uruguay, 1980)
0 patients with gastric poiyps were operated in the General Hospital far Acute_ Cases "J. M. Ramos Mejía", of Buenos Aires, between 1967 and 1977.